Formation and Activity of the Collection of the State Museum of Arts of the Republic of Karakalpakstan Named After I. V. Savitsky (Texas Journal of Philology, Culture and History, 2023)
This article writes about the formation of a unique collection of the Nukus Museum of Art by the founder, artist, archaeologist and ethnographer Igor Savitsky. The article also provides information about the folk arts and crafts of the Karakalpaks, fine arts and archaeological objects of Ancient Khorezm.